2000
DOI: 10.1099/0022-1317-49-11-1047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EDTA on the resistance of clinical isolates of Acinetobacter baumannii to the bactericidal activity of normal human serum

Abstract: Acinetobacter baumannii is an opportunist nosocomial pathogen of world-wide importance and produces severe infections in immunocompromised patients. However, the virulence factors contributing to its pathogenic properties are not well known. The effect of normal human serum against 18 clinical isolates of the most prevalent biotypes of A. baumannii in Chile was investigated. The effect of pre-treatment of the cells with ethylene diamine tetraacetic acid (EDTA) or bismuth subsalicylate (BSS), compounds known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Time between donation and experimental testing could facilitate platelet degradation. Additionally, the non-specific activity of the complement system and antigen-specific antibodies present in donor plasma could play an operative role [36,37]. Complement acts against non-self invaders by detecting pathogen-associated molecular patterns present on the surface of most bacteria [36].…”
Section: Resultsmentioning
confidence: 99%
“…Time between donation and experimental testing could facilitate platelet degradation. Additionally, the non-specific activity of the complement system and antigen-specific antibodies present in donor plasma could play an operative role [36,37]. Complement acts against non-self invaders by detecting pathogen-associated molecular patterns present on the surface of most bacteria [36].…”
Section: Resultsmentioning
confidence: 99%
“…(Hellwage et al, 2001;Hartmann et al, 2006). García et al (2000) reported that the serum resistance of A. baumannii was mainly due to lipopolysaccharides. These complement regulator-acquiring surface proteins contribute to persistence of bacteria in the hosts and to pathogenesis of Lyme disease.…”
Section: Discussionmentioning
confidence: 99%
“…The complement system is the host innate immune defense comprising a series of serum proteins that initiates the death of the bacterium through either lysis or opsonization. One of the mechanisms by which bacterial cells resist killing by serum compliments is by producing surface proteins that bind human factor H (FH), and thereby inhibit the deposition of complements on the bacterial surface (41,63). The mechanism by which Acinetobacter spp.…”
Section: Pathogenesis Virulence Factors and Resistancementioning
confidence: 99%